2022
DOI: 10.1093/tas/txac025
|View full text |Cite
|
Sign up to set email alerts
|

Board Invited Review: Crossbreeding beef × dairy cattle for the modern beef production system

Abstract: Current trends in the United States dairy industry suggest that crossbred beef × dairy calves are replacing a proportion of the calf-fed Holstein steers slaughtered for beef each year. Economic pressures value preweaned beef × dairy calves at a premium over preweaned dairy bull calves; however, there is little modern data to support that intensively fed crossbred calves maintain their premium value over dairy steers across the supply chain. Data from international production systems and from historic research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Feedlot closeout data were collected between 2015 and 2018, and carcass data were obtained from cattle slaughtered in 2019. Since these times, beef × dairy crossbreeding has become a much more widespread practice among U.S. dairies according to recent reports (National Association of Animal Breeders [NAAB], 2021 ; Baisel and Felix, 2022 ). Demand from dairies for beef semen from genetics supply companies has prompted considerable improvement in the type of beef genetics being supplied to produce beef × dairy crossbreds ( Baisel and Felix, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feedlot closeout data were collected between 2015 and 2018, and carcass data were obtained from cattle slaughtered in 2019. Since these times, beef × dairy crossbreeding has become a much more widespread practice among U.S. dairies according to recent reports (National Association of Animal Breeders [NAAB], 2021 ; Baisel and Felix, 2022 ). Demand from dairies for beef semen from genetics supply companies has prompted considerable improvement in the type of beef genetics being supplied to produce beef × dairy crossbreds ( Baisel and Felix, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since these times, beef × dairy crossbreeding has become a much more widespread practice among U.S. dairies according to recent reports (National Association of Animal Breeders [NAAB], 2021 ; Baisel and Felix, 2022 ). Demand from dairies for beef semen from genetics supply companies has prompted considerable improvement in the type of beef genetics being supplied to produce beef × dairy crossbreds ( Baisel and Felix, 2022 ). Many genetics supply companies have recently developed specific branded programs for genetics of beef sires best suited for producing crossbreds that optimize performance and profitability in the beef supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was conducted in a forage-finishing system and the majority of cattle in the United States are finished on grain-based diets because grain-finishing systems have long been reported to improve feed conversion relative to fiber or forage-based systems. Basiel and Felix (2022) summarized finishing systems for beef × dairy crosses and concluded that while beef × dairy cattle often gained more body weight, spent fewer days on feed, and were more feed efficient than dairy cattle finished on forage, they were less feed efficient than native beef cattle breeds. However, these authors reported the older nature of many of the studies they reviewed, and efficiency of finishing systems may warrant revisiting these results.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in beef semen sales has been largely attributed to the dairy industry because over 90% of beef females in the United States are mated exclusively by natural service ( USDA, 2020 ). The primary impetus for these mating decisions is to increase the value of surplus calves coming off the dairy farm ( Basiel and Felix, 2022 ). The value of beef × dairy calves exceeds that of purebred dairy bull calves ( McCabe et al., 2022 ), in some instances by several hundred dollars.…”
Section: Introductionmentioning
confidence: 99%